Respirometric kinetic parameter calculations of a batch jet loop bioreactor treating leachate and oxygen uptake rate estimation by DTM - Ince, M.; Yildiz, F.; Engin, G. Onkal; Engin, S. N.; Keskinler, B. (ELSEVIER, 2008)
A novel circulating jet loop bioreactor adapted for organic matter oxidation has been designed and constructed. In this study, the input was leachate samples collected from Kemerburgaz Odayeri waste landfill site located on the European side of Istanbul. Controlling the jet loop bioreactor to realize high rates of purification depends on maintaining the appropriate loadings and operating conditions. This requires collecting various system data to estimate the dynamics of the system satisfactorily with the aim of keeping certain parameters within the specified range. The differential transform method (DTM) based solution of the state equations reveals the current state of the process so that any deviation in the system parameters can be immediately detected and regulated accordingly. The respirometric method for kinetic parameter calculations for biodegradation has been used for some time. In many studies, the respirometer was designed separately, usually in bench-scale. However, when a separate respirometer is used, the scale effect and parameters that affect the hydrodynamic structure of the system should be taken into consideration. In this study, therefore, the jet loop reactor itself was used as a respirometer. Thus, the kinetic parameters found reflecting the characteristics of microorganisms used for biodegradation would be more realistic. If the main reactor, here the jet loop reactor, would be used as the respirometer, the kinetic parameter changes can easily be monitored in the long run. Using the bioreactor as a respirometer, the most important kinetic parameters, K-s, k(d) and mu(max) were found to be 11,000 mg L-1, 0.019 day(-1), and 0.21 day(-1), respectively. The stoichiometric coefficient, Y, was found to be 0.28 gr gr(-1) for the present system. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: respirometric kinetic parameters; jet loop bioreactor; leachate treatment; differential transform method; ACTIVATED-SLUDGE; MASS-TRANSFER; MEMBRANE BIOREACTOR; WASTE LANDFILL; NITRIFICATION; PERFORMANCE; RESPIRATION; REMOVAL; Engineering; Environmental Sciences & Ecology